2009
DOI: 10.1373/clinchem.2008.119396
|View full text |Cite
|
Sign up to set email alerts
|

uPA+/+-SCID Mouse with Humanized Liver as a Model for In Vivo Metabolism of Exogenous Steroids: Methandienone as a Case Study

Abstract: Background: Adequate detection of designer steroids in the urine of athletes is still a challenge in doping control analysis and requires knowledge of steroid metabolism. In this study we investigated whether uPA+/+-SCID mice carrying functional primary human hepatocytes in their liver would provide a suitable alternative small animal model for the investigation of human steroid metabolism in vivo. Methods: A quantitative method based on liquid chromatography–tandem mass spectrometry (LC-MS/MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Apart from being susceptible to human hepatotropic microorganisms these mice also express a humanized drug metabolism [38-42]. This will accelerate and reduce the costs of the development of new strategies to prevent and treat the pre-erythrocytic stage of malaria before these are tested in human volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being susceptible to human hepatotropic microorganisms these mice also express a humanized drug metabolism [38-42]. This will accelerate and reduce the costs of the development of new strategies to prevent and treat the pre-erythrocytic stage of malaria before these are tested in human volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of LTMs of different anabolic steroids was accomplished by means of several different methodologies including fractionation and in-depth elucidation of urine samples collected from human administration studies6 7 and animal model elimination studies 8 9. A novel approach was recently presented, which is based on the administration of deuterated steroids followed by the identification of the respective deuterated urinary metabolites using hydrogen isotope ratio mass spectrometry 10.…”
Section: Introductionmentioning
confidence: 99%
“…This model has superior qualities compared to other in vivo or in vitro models to perform metabolic studies due to its excellent correlation with the human liver [8]. Previous studies have demonstrated that the steroids administered to these chimeric mice underwent approximately the same metabolic transformations as in human subjects [8][9][10][11]. In this way the in vivo human metabolism of illicit substances can be studied without involving human volunteers.…”
Section: Introductionmentioning
confidence: 99%